2022
DOI: 10.1007/s00405-022-07481-w
|View full text |Cite
|
Sign up to set email alerts
|

Acinic cell carcinoma of the parotid gland: Timeo Danaos et dona ferentes? A multicenter retrospective analysis focusing on survival outcome

Abstract: Objectives To analyze the demographic data, surgical and adjuvant treatment data and the survival outcomes in adult patients affected by acinic cell carcinoma of the parotid gland (AciCC). Methods A retrospective multicenter analysis of patients treated for AciCC of the parotid gland from 2000 to 2021 was performed. Exclusion criteria were pediatric (0–18 years) patients, the absence of follow-up and patients with secondary metastatic disease to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We have already shown that recurrence or metastasis, as well as age >65 years, are independent prognostic indicators of tumor aggressiveness [9]. In contrast to other authors [10,11], we showed that the HG phenotype could not be predictive of recurrence or more aggressive behavior.…”
Section: Introductioncontrasting
confidence: 97%
“…We have already shown that recurrence or metastasis, as well as age >65 years, are independent prognostic indicators of tumor aggressiveness [9]. In contrast to other authors [10,11], we showed that the HG phenotype could not be predictive of recurrence or more aggressive behavior.…”
Section: Introductioncontrasting
confidence: 97%
“…Indeed, there are not systematic reviews or meta-analysis on the role of RT in parotid gland sarcomas. For epithelial malignant neoplasms of the parotid gland (mucoepidermoid carcinoma, carcinoma ex pleomorphic adenoma, adenoid cystic carcinoma, salivary duct carcinoma, and acinic cell carcinoma), adjuvant RT is taken into consideration in high histological grade, microscopic or macroscopic residual disease, perineural or lymphovascular invasion, T3-4 stage disease and/or positive lymph nodes [15][16][17]. Typically, malignant mesenchymal tumors are described as not sensitive to RT because neoplastic cells, through several mechanisms, may escape from RT-mediated cell death [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of parotid tumors, mucoepidermoid carcinoma is the most common, followed by adenoid cystic carcinoma and acinic cell carcinoma [ 2 ]. These tumors present a wide and complex range of biological behaviors and are morphologically heterogeneous, making histopathological diagnosis challenging [ 3 ]. The World Health Organization (WHO) has recently updated the classification of SGCs by introducing molecular data to define new entities [ 4 ]; however, molecular typing in this field is still in progress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%